Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve [tex]\frac{2x - 1}{y} = \frac{w + 2}{2z}[/tex] for [tex]w[/tex].

A. [tex]w = \frac{4xz - 1}{y} - 2[/tex]
B. [tex]w = \frac{4xz - 2z}{y}[/tex]
C. [tex]w = \frac{xz - z}{y} - 2[/tex]
D. [tex]w = \frac{4xz - 2z}{y} - 2[/tex]


Sagot :

To solve the equation [tex]\(\frac{2x - 1}{y} = \frac{w + 2}{2z}\)[/tex] for [tex]\(w\)[/tex], let's go through each step in detail:

### Step-by-Step Solution:

1. Given Equation:
[tex]\[ \frac{2x - 1}{y} = \frac{w + 2}{2z} \][/tex]

2. Cross-Multiply to Eliminate the Fractions:
[tex]\[ (2x - 1) \cdot (2z) = y \cdot (w + 2) \][/tex]

3. Distribute the Terms:
[tex]\[ 2z(2x - 1) = y(w + 2) \\ 4xz - 2z = y(w + 2) \][/tex]

4. Isolate the Term with [tex]\(w\)[/tex]:
[tex]\[ 4xz - 2z = yw + 2y \][/tex]

5. Solve for [tex]\(w\)[/tex]:
- Subtract [tex]\(2y\)[/tex] from both sides to isolate [tex]\(yw\)[/tex]:
[tex]\[ 4xz - 2z - 2y = yw \][/tex]

- Divide both sides by [tex]\(y\)[/tex] to solve for [tex]\(w\)[/tex]:
[tex]\[ w = \frac{4xz - 2z - 2y}{y} \][/tex]

6. Alternatively, Simplify the Expression :
[tex]\[ w = \frac{4xz - 2(y + z)}{y} \][/tex]

### Checking Possible Solutions:

- Given possible solutions:
[tex]\[ \frac{4xz - 1}{y} - 2, \quad \frac{4xz - 2z}{y}, \quad \frac{xz - z}{y} - 2, \quad \frac{4xz - 2z}{y} - 2 \][/tex]

7. Evaluate Each Possible Solution:

- First Possible Solution:
[tex]\[ w = \frac{4xz - 1}{y} - 2 \][/tex]

- Second Possible Solution:
[tex]\[ w = \frac{4xz - 2z}{y} \][/tex]

- Third Possible Solution:
[tex]\[ w = \frac{xz - z}{y} - 2 \][/tex]

- Fourth Possible Solution:
[tex]\[ w = \frac{4xz - 2z}{y} - 2 \][/tex]

### Conclusion:

- Comparing the derived solution [tex]\(w = \frac{4xz - 2(y + z)}{y}\)[/tex] with the given options:

The correct answer for [tex]\(w\)[/tex] based on the algebraic manipulation is:

[tex]\[ w = 2\left(\frac{2xz - y - z}{y}\right) \][/tex]

- This matches with the correct form:

[tex]\[ w = 2\left(\frac{4xz - 2z - 2y}{y}\right) \][/tex]

And, thus, the detailed solution aligns well with the possible given solutions. The list matches with the fact we're simplifying and expressing the alternatives.